2011
DOI: 10.1186/1471-2458-11-s5-s7
|View full text |Cite
|
Sign up to set email alerts
|

Looking back in time: conducting a cohort study of the long-term effects of treatment of adolescent tall girls with synthetic hormones

Abstract: ObjectivePublic health research is an endeavour that often involves multiple relationships, far-reaching collaborations, divergent expectations and various outcomes. Using the Tall Girls Study as a case study, this paper will present and discuss a number of methodological, ethical and legal challenges that have implications for other public health research.ApproachThe Tall Girls Study was the first study to examine the long-term health and psychosocial effects of oestrogen treatment for tall stature.ResultsIn … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 33 publications
0
7
0
Order By: Relevance
“…Eleven studies used qualitative or survey methods to obtain input from patients, 4,7,[18][19][20][21][22][23][24][25][26] and 17 studies were narrative reports describing one group's experiences with engagement. [27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43] The remaining seven studies were descriptions of specific initiatives reported on websites [44][45][46][47][48][49][50] ( Table 1 and Table 2). The studies were mostly conducted in North America and Europe, and most focused on a specific rare disease rather than rare diseases in general.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Eleven studies used qualitative or survey methods to obtain input from patients, 4,7,[18][19][20][21][22][23][24][25][26] and 17 studies were narrative reports describing one group's experiences with engagement. [27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43] The remaining seven studies were descriptions of specific initiatives reported on websites [44][45][46][47][48][49][50] ( Table 1 and Table 2). The studies were mostly conducted in North America and Europe, and most focused on a specific rare disease rather than rare diseases in general.…”
Section: Resultsmentioning
confidence: 99%
“…cians. 20,38,39,47,49 Seven studies were classified as sufficiently descriptive 7,18,19,[23][24][25][26] The purposes of engagement included identifying patient-centered research topics or agendas, 19,23,29,36,39 identifying outcomes important to patients or developing measures relevant to patients' needs, 7,19,20,23,25,26 increasing recruitment or enrollment through development of patient-centered study designs, 4,18,21,24,27,30,31,41 and incorporating the patient perspective into study design 19,25,35,39,40 (Table 2, Table 3). Patients and other stakeholders were most commonly engaged in the preparatory stage (n= 19 for agenda setting) 4, 7, 19, 20, 23, 25, 28, 29, 32, 35, 36, 39- (Table 4 [online]).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations